Some New Fractional-Calculus Connections between Mittag-Leffler Functions - Srivastava, Hari M.; Fernandez, Arran; Baleanu, Dumitru (Mdpi, 2019)
We consider the well-known Mittag-Leffler functions of one, two and three parameters, and establish some new connections between them using fractional calculus. In particular, we express the three-parameter Mittag-Leffler function as a fractional derivative of the two-parameter Mittag-Leffler function, which is in turn a fractional integral of the one-parameter Mittag-Leffler function. Hence, we derive an integral expression for the three-parameter one in terms of the one-parameter one. We discuss the importance and applications of all three Mittag-Leffler functions, with a view to potential applications of our results in making certain types of experimental data much easier to analyse.
Keywords: fractional integrals; fractional derivatives; Mittag-Leffler functions